Debris Apically Extruded by Two Reciprocating Systems: A Comparative Quantitative Study - Amaral, Andressa Pinho; Limongi, Patrícia Bastos Oliveira Conceição; Fontana, Carlos Eduardo; Martin, Alexandre Sigrist De; Bueno, Carlos Eduardo Da Silveira; Pinheiro, Sérgio Luiz (European Journal of Dentistry, 2019)
Objective The objective of this study was to quantify the amount of debris apically extruded after instrumentation with two reciprocating systems.Materials and Methods Forty-two single-rooted mandibular premolars with only one straight root canal and apical diameter compatible with a no. 15 K-file were randomly divided into two groups (n = 21) according to the instrument used: ProDesign R (Easy Equipamentos; Belo Horizonte, Minas Gerais, Brazil) and Reciproc Blue (VDW; Munich, Germany). Dry Eppendorf tubes were weighed three consecutive times for the initial mean weight. A silicone stopper was then fitted into the mouth of the tube. Each tooth was inserted through the stopper up to the cementoenamel junction and instrumented with one of the two systems to the predetermined working length (18 mm). The root canals were instrumented per root thirds. At each instrumented root third, the canal was irrigated with 3 mL of double-distilled water, followed by patency control. Each stopper was then separated from the tube and tubes were incubated at 70°C for 5 days. Tubes were again weighed, and the amount of extruded debris was calculated by subtracting the initial mean weight from the final mean weight.Statistical Analysis Results were analyzed using the Mann–Whitney test at a 5% significance level.Results No significant difference was observed in debris extrusion between the ProDesign R and Reciproc Blue systems (p = 0.7557).Conclusions The two reciprocating systems tested produced similar amounts of postinstrumentation apically extruded debris.
Keywords: apical extrusion; root canal preparation; endodontics